Character Education Values That Work in Islamic Senior High School Setting - Yaumi, Muhammad; Husain, Rustam (Al-Ulum, 2015)
The purpose of study is to discover the character education values that are integrated in lesson plan, implemented in the classroom setting, and classroom academic rules. This is a case study research that focused on describing the integration of character education program in the Model Islamic senior high school of Makassar, Indonesia. Fifty lesson plans were collected, twenty six informants were observed, and five informants were interviewed to have data on character education values that work. The data were analyzed using qualitative approach; data reduction, data display, conclusion, and verification. The result showed that (1) there are eighteen character education values written in the lesson plan; religious, honest, tolerant, discipline, hard working, creative, independent, democratic, curiosity, the spirit of nationalism, love to motherland,Â  appreciation of achievement, friendly, peaceful, love to read, environmental and social care, responsibility, (2) the values that work in the classroom are religious, trustworthy, respectfulness, diligent, fair, care, integrity, responsible, honest, love to motherland, courage, and (3) the values that work in the academic rules are disciplines, care, tolerant, friendly, responsible.-----Studi ini bertujuan untuk menemukan nilai-nilai pendidikan karakter yang diintegrasikan melalui Rencana Pelaksanaan Pembelajaran, diimplementasikan dalam pelaksanaan pembelajaran di kelas dan aturan akademik sekolah. Penelitian ini menggunakan metode studi kasus yang diarahkan pada pendeskripsian integrasi program pendidikan karakter pada Madasah Aliyah Negeri Model Makassar, Indonesia. Sebanyak 50 RPP dikumpulkan, duapuluh enam informan diamati, dan lima informan diwawancarai untuk memperoleh data tentang nilai-nilai karakter yang dijalankan. Data dianalisis dengan menggunakan pendekatan kualitiatif; reduksi data, penyajian data, verifikasi, dan pengambilan kesimpulan. Hasil penelitian menunjukkan bahwa (1) terdapat delapan belas karakter yang tertulis pada RPP mencakup religius, jujur, toleran, disiplin, kerja keras, kreatif, mandiri, demokratis, keingintahuan, semangat kebangsaan, cinta tanah air, menghargai prestasi, bersahabat, cinta damai, gemar membaca, peduli lingkungan, peduli sosial, dan bertanggungjawab, (2) nilai-nilai karakter yang diintegrasikan dalam ruang kelas adalah religius,amanah, hormat, rajin, adil, peduli, integritas, bertanggungjawab, jujur, cinta tanah air, keberanian, dan (3) nilai-nilai karakter dalam penegakkan aturan sekolah adalah disiplin, peduli, toleran, bersahabat, dan bertanggungjawab.Â